Crowdsourcing interventions to promote uptake of COVID-19 booster vaccines - Robert Böhm; Cornelia Betsch; Yana Litovsky; Philipp Sprengholz; Noel Brewer; Gretchen B. Chapman; Julie Leask; George Loewenstein; Martha Scherzer; Cass R. Sunstein; Michael Kirchler (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2022)
We apply a novel crowdsourcing approach to provide rapid insights on the most promising interventions to promote uptake of COVID-19 booster vaccines. In the first stage, international experts proposed 46 unique interventions. To reduce noise and potential bias, in the second stage, experts and representative general population samples from the UK and the US rated the proposed interventions on several criteria, including expected effectiveness and acceptability. Sanctions were evaluated as potentially most effective but least accepted. Interventions that received the most positive evaluations regarding both effectiveness and acceptability across evaluation groups were a day off after getting vaccinated, financial incentives, tax benefits, benefit campaigns, and mobile vaccination teams. The results provide useful insights to help governments in their decision which interventions to implement.
Keywords: 330; booster vaccination; COVID-19; interventions